2020
DOI: 10.1111/ors.12546
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal cancer and osteoradionecrosis in a novel radiation era: a single institution analysis

Abstract: Aim: This study investigates the incidence of osteoradionecrosis (ORN) in patients with oropharyngeal cancer (OPC) since the use of intensitymodulating radiation therapy (IMRT). Materials and methods: The multi-disciplinary log for head and neck cancer (HNC) at Guys & St Thomas' NHS Foundation Trust was used to identify and collect data on all patients with OPC and treated with a curative intent. Basic and oncology-related demographic data were collected retrospectively. The presence and absence of ORN along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…5 With the rising incidence of human papillomavirus (HPV) associated subtypes of HNC, 6 survival rates have improved, as HPV-associated tumors are more sensitive to radiation therapy (RT) than HPV-negative tumors and exhibit improved tumor control. [7][8][9] Moreover, because patients with HPV-positive tumors are typically younger and healthier, 10 the longer life-years expectancy postradiation and expected chronic compromise to bone healing for these patients result in a higher cumulative lifetime risk for ORN development, 11 highlighting the importance of dedicated strategies aimed to prevent ORN in modern practice.…”
Section: Introductionmentioning
confidence: 99%
“…5 With the rising incidence of human papillomavirus (HPV) associated subtypes of HNC, 6 survival rates have improved, as HPV-associated tumors are more sensitive to radiation therapy (RT) than HPV-negative tumors and exhibit improved tumor control. [7][8][9] Moreover, because patients with HPV-positive tumors are typically younger and healthier, 10 the longer life-years expectancy postradiation and expected chronic compromise to bone healing for these patients result in a higher cumulative lifetime risk for ORN development, 11 highlighting the importance of dedicated strategies aimed to prevent ORN in modern practice.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond this early-phase ORN in OPC, they also experience a lifelong risk of ORN of steady risk with the need for extractions in the future. 26,27,45 The current study identified 32 patients (16.2%) with maxillary ORN, highlighting it occurrence is a real entity and requires appropriate recognition. Many definitions still in place for ORN are historic and refer explicitly to only mandibular ORN.…”
Section: Discussionmentioning
confidence: 83%
“…This aspiration has not been achieved with the suspicion that rates of ORN may have increased especially in the OPC group. 18,19 It is argued that with IMRT all areas of the mouth become a target for some degree of exposure which explains the late effects not often seen previously. 20,21 Traditionally ORN has been associated maximum RT doses >60 to 75 Gy 6,15 ; however, it is now conceded that doses exceeding in the range of 30-40 Gy place patients at "at risk" of ORN.…”
Section: Discussionmentioning
confidence: 99%
“…24 The sensitivity of OPC to radiation produces improved long term survival but with it an opportunity to develop ORN with a compromised but heavily restored mouth and may explain the increase of this complication in OPC patients. 12,19 It has always been appreciated that the molar teeth were at risk following RT and extraction carried a threat of ushering in ORN. This remains the case, but the data presented shows that attention should be paid to the whole dentition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation